Peran Gizi terhadap Kesehatan Reproduksi Wanita Kajian Literatur Review - Syamsu, Rachmat Faisal; Bonita, Nita; Alimun, Sity Rahmatia (Universitas Batanghari Jambi, 2025)
This study aims to evaluate scientific evidence on the role of nutrition in women's reproductive health through a comprehensive literature analysis. The research method used is a literature review, which examines articles from PubMed, NCBI, Google Scholar, and other international databases during 2015–2025 that meet the following criteria: full-text, open access, international journals SINTA 3-5, and discussing the relationship between nutrition and women's reproductive health. The results show that optimal nutritional status plays a central role in women's reproductive health through hormonal regulation, ovarian function, and endometrial readiness. Appropriate nutritional interventions can improve natural fertility and the success rate of assisted reproductive technologies. A personalized nutritional approach based on an individual's metabolic profile is needed to optimize reproductive health.